Experimental Research and Development of Nonlinearity Models for FR1 Range Mixers for Electromagnetic Compatibility Analysis - E. V. Sinkevich; V. I. Mordachev; Wan Fayu; D. A. Tsyanenka; I. V. Shakinka (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2025)
By using the technology of double-frequency testing, an experimental analysis of nonlinear properties of low-power radio-frequency mixers is performed at frequencies of the n7 band allocated in Belarus for 4G mobile communication systems and the n78 band that is planned to be used in Belarus for 5G mobile communications. Based on the results of the measurements of mixer characteristics (the double-frequency characteristics, single-tone amplitude characteristics, as well as two-tone amplitude characteristics and dynamic ranges for 3rd-, 5th-, 7th-, and 9th-order intermodulation) in the harmonic zone of the useful signal, high-order polynomial models describing the transfer characteristics of the considered mixers are synthesized. These models are intended to analyze the effect of radio-frequency electromagnetic interference on radio links behavior in case of a large dynamic range of input signals by using the discrete nonlinear modeling technique. The obtained models provide high adequacy and computational efficiency of quantitative analysis of nonlinear processes and radio interference occurring in receivers of 4G/5G/6G radio networks in a complex electromagnetic environment.